2021
DOI: 10.1049/mia2.12068
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of numerical dispersion with time step of the FDTD methods: avoiding erroneous conclusions

Abstract: To obtain high accuracy and efficiency in the simulations, an optimum time step should be taken in finite-difference time-domain (FDTD) methods. The authors investigated how time steps impact on numerical dispersion of two FDTD methods including the FDTD(2,2) method and the FDTD(2,4) method. Through rigorously analytical and numerical analysis, it is found that small time steps of the FDTD methods do not always have small numerical errors. Our findings reveal that these two FDTD methods present different behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Also, the FDTD method is widely used in electromagnetic field analysis, such as for specific absorption rate (SAR) evaluation, so the reliability of the FDTD method can be confirmed from several related works [20,21]. An error analysis of the FDTD method was conducted in [22], where it was shown that the FDTD calculation can achieve an acceptable calculation error in a numerical model. A model used in our electromagnetic field simulation is shown in Figure 1 and the parameters used are shown in Table 1.…”
Section: Examination Of Various Parameters Using Electromagnetic Fiel...mentioning
confidence: 99%
“…Also, the FDTD method is widely used in electromagnetic field analysis, such as for specific absorption rate (SAR) evaluation, so the reliability of the FDTD method can be confirmed from several related works [20,21]. An error analysis of the FDTD method was conducted in [22], where it was shown that the FDTD calculation can achieve an acceptable calculation error in a numerical model. A model used in our electromagnetic field simulation is shown in Figure 1 and the parameters used are shown in Table 1.…”
Section: Examination Of Various Parameters Using Electromagnetic Fiel...mentioning
confidence: 99%
“…Figure 3 also shows that both SE frequency dependencies have unphysical oscillations which are caused by the numerical dispersion of the FDTD method. This issue arises from the difference between wave propagation in the actual physical medium and in the discrete FDTD mesh and can be reduced by increasing computational cost [40]. Henceforward, we decided not to eliminate the errors associated with the numerical dispersion since the achieved calculation accuracy is sufficient for this study.…”
Section: Simulation Of Shield System Elementsmentioning
confidence: 99%
“…The values of the electric and magnetic fields are calculated at each point of the structure and at each instant. The time steps lead to small numerical errors, but at long times the numerical dispersion can severely degrade the accuracy and even be totally unacceptable [85]. The DDA has been extended to the temporal regime.…”
Section: Dda In Time Domainmentioning
confidence: 99%